APPLYING GENDER DIFFERENCES IN PHONOLOGICAL AWARENESS TO ENHANCE STUDENTS’ READING ABILITY - Winarto, Eline Rozaliya; Aprianti, Fitri (University of Kuningan, 2023)
Phonological awareness is the first stage in enhancing kids' reading skills. Phonological awareness provides the foundation for youngsters to associate written letters with their voices, which will help them understand the reading process. Primary school reading abilities provide the groundwork for subsequent reading success. The research technique that utilized to conduct study on phonological awareness and reading ability of male and female primary school pupils is a research method that combines quantitative and qualitative data, commonly known as the Mixed-Method. To obtain quantitative data, this method employs one experimental group, whereas to obtain qualitative data, classroom observation, questionnaires, and interviews conducted on experimental. The subjects of this study were low-grade male and female pupils at primary schools in Cirebon. A basic random sampling procedure is used to determine the samples. There were four types of data gathering procedures used in this study: phonological awareness, observation, questionnaires, and interviews. This study leads to several findings. First, the findings are broadly consistent with previous research in the field of PA in primary children. The study discovered a consistent developmental trajectory in the majority of the PA tasks in favor of primary children. In addition, females outperformed males in some PA subtests. In order to eliminate obstacles to advancing their reading abilities, elementary students must be trained on PA exercises.